2020
DOI: 10.1021/acs.jpcc.0c01122
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Optical and Photoluminescence Bistable Responses Accompanied by Tunable Dielectric Behaviors in Crown Inclusions

Abstract: Two host–guest inclusion compounds, [(4-fluorobenzylammonium)­(18-crown-6)]­[ClO4] (1) and [(4-chlorobenzylammonium)­(18-crown-6)]­[ClO4] (2), are found to undergo reversible phase transitions, which enable them to achieve quadratic nonlinear optical (NLO) and photoluminescence bistable switching response characteristics associated with the order–disorder transition of the ClO4 – anions and the coordination environment between the host and guest. By a reasonable selection of suitable organic cations, the regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…In addition, the change in the anionic framework has caused a structural distortion which may lead to a change in the molecular dipole moment and increased polarity of the structure. The gradual increase in SHG intensity from (FMTMA)­PbI 3 to (FMTMA)­PbBr 2 I to (FMTMA)­PbCl 2 I may be caused by the variation in dipole moments and polarizations, which are closely related to the SHG characteristics . On the basis of the point charge models of their crystal structures (Figure S5), the spontaneous polarization values of (FMTMA)­PbI 3 , (FMTMA)­PbBr 2 I, and (FMTMA)­PbCl 2 I can be estimated to be 0.005, 0.354, and 0.511 μC cm –2 , respectively, and the corresponding dipole moments in a structural unit cell were estimated to be 0.0103 × 10 –29 , 0.7097 × 10 –29 , and 0.9503 × 10 –29 C m, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the change in the anionic framework has caused a structural distortion which may lead to a change in the molecular dipole moment and increased polarity of the structure. The gradual increase in SHG intensity from (FMTMA)­PbI 3 to (FMTMA)­PbBr 2 I to (FMTMA)­PbCl 2 I may be caused by the variation in dipole moments and polarizations, which are closely related to the SHG characteristics . On the basis of the point charge models of their crystal structures (Figure S5), the spontaneous polarization values of (FMTMA)­PbI 3 , (FMTMA)­PbBr 2 I, and (FMTMA)­PbCl 2 I can be estimated to be 0.005, 0.354, and 0.511 μC cm –2 , respectively, and the corresponding dipole moments in a structural unit cell were estimated to be 0.0103 × 10 –29 , 0.7097 × 10 –29 , and 0.9503 × 10 –29 C m, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Tang et al not only reported the dynamics of the ferroelastic phase transition for [(H 3 O)(18-Crown-6)]PF 6 , but also observed its ferroelastic domain patterns. 33 The compound shows a higher ferroelastic-paraelastic phase transition temperature (T c = 287.2 K) compared to other reports, but it is still lower than room temperature. 10,33,37 This means that the reported crown ether-based compounds might not be suitable for commercial application.…”
mentioning
confidence: 61%
“…33 The compound shows a higher ferroelastic-paraelastic phase transition temperature (T c = 287.2 K) compared to other reports, but it is still lower than room temperature. 10,33,37 This means that the reported crown ether-based compounds might not be suitable for commercial application. Inspiringly, in the exploration of the molecular ferroelectrics, the ''momentum matching'' strategy implying a proper balance between building blocks has been successfully employed in designing molecular ferroelectrics with excellent performance.…”
mentioning
confidence: 61%
See 2 more Smart Citations